Instilling Character Education Values through the Pancasila Student Profile Program (P5) in the Independent Curriculum at Bina Putra Seputih Agung Middle School - Sidiq, Syahrul; Irhamudin, Irhamudin; Wijaya, Adi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The implementation of the Projek Penguatan Profil Pelajar Pancasila (P5) at SMP Bina Putra Seputih Agung serves as a strategic platform for internalizing character education values among students within the framework of the Kurikulum Merdeka. This study is motivated by the growing phenomenon of moral decline and decreasing discipline among students as a consequence of globalization. The research focuses on exploring the process of character value cultivation through the application of P5, while also identifying potential challenges in its implementation. Employing a qualitative descriptive methodology, data collection was conducted through in-depth interviews, participant observation, and document analysis. The findings indicate that P5 holds significant potential in fostering essential character values—such as collaboration, responsibility, and individual independence—through project-based activities. Nevertheless, its implementation continues to face several challenges, including limited time allocation and insufficient teacher training. Therefore, strengthening strategies and fostering synergy among key stakeholders are required to optimize the role of P5 as an effective medium for character education in schools